2016
DOI: 10.1071/sr15332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced efficiency fertilisers on nitrous oxide emissions in a sub-tropical cereal cropping system

Abstract: Abstract.To meet the global food demand in the coming decades, crop yields per unit area must increase. This can only be achieved by a further intensification of existing cropping systems and will require even higher inputs of N fertilisers, which may result in increased losses of nitrous oxide (N 2 O) from cropped soils. Enhanced efficiency fertilisers (EEFs) have been promoted as a potential strategy to mitigate N 2 O emissions and improve nitrogen use efficiency (NUE) in cereal cropping systems. However, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…Notably, the substantial rainfall events later in the cropping season (178 mm fell from mid-February to mid-April 2014 at the Oxisol site) did not generate high N 2 O emissions, indicating that by then most of the applied N was probably taken up by plants, immobilised by microbes, lost to the environment or deeper in the soil profile. These observations of the majority of N 2 O emissions being recorded within 90 days from fertilisation are in good agreement with the results of other studies on Australian subtropical summer cropping systems on Vertisols and Oxisols (Scheer et al 2013(Scheer et al , 2016bDe Antoni Migliorati et al 2014).…”
Section: Effects Of Weather Events On Seasonal N Dynamicssupporting
confidence: 81%
See 1 more Smart Citation
“…Notably, the substantial rainfall events later in the cropping season (178 mm fell from mid-February to mid-April 2014 at the Oxisol site) did not generate high N 2 O emissions, indicating that by then most of the applied N was probably taken up by plants, immobilised by microbes, lost to the environment or deeper in the soil profile. These observations of the majority of N 2 O emissions being recorded within 90 days from fertilisation are in good agreement with the results of other studies on Australian subtropical summer cropping systems on Vertisols and Oxisols (Scheer et al 2013(Scheer et al , 2016bDe Antoni Migliorati et al 2014).…”
Section: Effects Of Weather Events On Seasonal N Dynamicssupporting
confidence: 81%
“…These were 160 and 120 kg N ha -1 on the Vertisol and Oxisol respectively. These rates were~30% higher than standard farmer practice (~120 and 90 kg N ha -1 respectively), but considered appropriate due to the preceding very wet summer with large denitrification losses Scheer et al 2016b) and the use of winter forage crops to ensure low starting profile N. * Urea (UREA-R): in both soils conventional urea was applied at a reduced rate (80 kg N ha -1 ) that was more comparable to standard farming practice in each region. The N rate was reduced to assess crop response and N 2 O emissions at suboptimal N rates.…”
Section: Study Sitesmentioning
confidence: 99%
“…Soil sampling conducted 1 month after sowing found less mineral N in the soil than would be expected from the amount added in fertiliser, indicating substantial N loss from the surface soil through denitrification and nitrate leaching. Because the N-fertilised soil did not affect postharvest N 2 O emissions, the critical period for N 2 O loss was the first 2-3 months after application of N fertiliser (Scheer et al 2016). By contrast, the N fertiliser applied at the 2011 sowing remained largely intact as soil mineral N for the next 2 months due to below-average moisture conditions (Fig.…”
Section: N 2 O Emissions In Relation To Rainfed Grain Productionmentioning
confidence: 99%
“…A contradiction therefore exists between how DMPP can decrease N 2 O emission by over 60% De Antoni Migliorati et al 2015;Scheer et al 2016), but only nominally increases grain yield. The explanation may partly lie in the higher N application rates.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of nitrification inhibitors (and other EEFs) have been demonstrated to be strongly dependent on site-specific conditions, soil texture and climate (Irigoyen et al 2003). Reduction in N 2 O emissions over the summer period from the use of DMPP-treated urea has been substantial De Antoni Migliorati et al 2015;Scheer et al 2016); however, there are no published studies evaluating the agronomic impacts of DMPP-treated urea on grain sorghum production in subtropical environments. Our study found that DMPP had a nominal grain yield advantage when considered over all the research sites in this study and this was only apparent at the higher fertiliser N application rates (Fig.…”
Section: Discussionmentioning
confidence: 99%